Exploring the therapeutic potential of volatile bioactive compounds from different parts of Tinospora cordifolia: a gas chromatography-mass spectrometry (GC-MS) study: Therapeutic potential of bioactive compounds from Tinospora - Akhilraj, B C; Suresh, J; Rajamani, K; Kumar, M; Gnanam , R (Journal of Spices and Aromatic Crops, 2023)
Chemicals utilised in the pharmaceutical business can be found in large quantities in medicinal plants. Crude plant herbal extracts are frequently utilised because they combine a variety of secondary metabolites or phytochemical elements with significant therapeutic potential. The main objective of this research was to identify the medicinally significant phytoconstituents from different economic parts of Tinospora cordifolia employing GC-MS. The stem, leaf, and root, respectively, had a total of 93, 74, and 53 peaks, which translates to a sizable number of phytocompounds with therapeutic value. Our results show that oleic acid, columbin, 10E,12Z-octadecadienoic acid, 9- octadecenoic acid (Z), 2, 3 - dihydroxypropyl ester, n-hexadecanoic acid, and 9,12,15-octadeca trieno were found in various parts of T. cordifolia. The results provide credence to the use of Tinospora cordifolia in conventional medical practice for a range of ailments.